Analisis Faktor Erodibilitas Tanah Penyebab Erosi di Area Tambang Batubara Site Melak - Arisdiansyah Putra; Ratna Widyaningsih; Mohammad Nurcholis (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2019)
Open-pit coal mining as done by the coal mining site Melak have a impact on the surrounding natural environment. The impact of mining operations is that the land becomes unproductive and erosion is very high because of loosing its vegetation on ex-mining land. Vegetation influence the sensitivity of the soil to withstand destruction and transportation by rain and surface runoff and the occurrence of landslides. Analysis of soil erodibility factors seen from the physical-chemical properties of soil is one of the causes of erosion by using organic element parameters, soil structure, permeability, texture. The observation location was carried out on the disposal slope and low wall in-pit that has been revegetation with the hydroseeding technique. This research was carried out by making a design of erosion and sedimentation plots in the form of a zinc boundary measuring 2 x 2 m2, each box divides into three columns. The division of three columns in each box is done to get representative repetition data. Taking soil samples is carried out in each box using a sample ring.